Tinjauan Mengenai Kedudukan Bank Sebagai Pihak Kreditur Pemegang Hak Tanggungan Atas Tanah Yang Musnah Akibat Bencana Alam - Sugianto, Kurniawan; Putra, Mohamad Fajri Mekka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Natural disasters in fact can result in the owner of land rights losing the right to control, use, or take advantage of the land, because the land is lost partially or completely. In addition to the land owner, losses due to the loss of land due to natural disasters can also be suffered by the creditors of the Bank as the holder of the mortgage right of the land that is the object of the mortgage due to the debt agreement. In this case, the debtor cannot be blamed for the destruction of the object or objects that are encumbered with the mortgage and are destroyed by a natural disaster, because when and where the disaster occurs is unpredictable and beyond the control of the parties, this is a state of coercion or overmacht/forje majeur. Therefore, through the normative juridical research method, the author will analyze the position of the bank's creditors and the existence of mortgage rights on land destroyed due to natural disasters, along with the position of creditors and debtors in the debt agreement that has been made.